LIMITATIONS ON THE EXCLUSIVE RIGHTS OF INTELLECTUAL PROPERTY RIGHT HOLDERS (SOCIAL JUSTICE PERSPECTIVE) - Sigit Nugroho (Al-Adl : Jurnal Hukum, 2023)
Social justice is the goal of the Indonesian state, which must be realized in all fields so that welfare is realized for all Indonesian people which also radiates in the field of intellectual property law, bearing in mind that the initial regulation of intellectual property came from developed countries which are industrial countries which are different from Indonesia. Social justice is the fundamental norm as well as the goal of the state, which is used as a reference in the formation of intellectual property law rules. Thus, arrangements regarding the distribution of intellectual property rights must pay attention to the public interest. Based on such arguments, the regulation regarding restrictions on the exclusive rights of intellectual property rights holders is realized in the public interest. At the implementation level, setting the exclusive rights of older intellectual property law protected without prejudice to the protection of community (general) rights as a form of limiting these rights for the common good. Restrictions on the exclusive rights of the holder of intellectual property law as a form of social justice have been regulated in the Indonesian legal system, although there are still deficiencies.